Upper critical solution temperature thermo-responsive polymer brushes and a mechanism for controlled cell attachment - Xue, Xuan; Thiagarajan, Lalitha; Braim, Shwana; Saunders, Brian R.; Shakesheff, Kevin M.; Alexander, Cameron (Royal Society of Chemistry, 2017)
We report the synthesis of thermo-responsive polymer brushes with Upper Critical Solution Temperature (UCST)-type behaviour on glass to provide a new means to control cell attachment. Thermoresponsive poly(N-acryloyl glycinamide)-stat-poly(N-phenylacrylamide) (PNAGAm-PNPhAm) brushes with three different monomer ratios were synthesized to give tunable phase transition temperatures (Tp) in solution. Surface energies of surface-grafted brushes of these polymers at 25, 32, 37 and 50 C were calculated from contact angle measurements and atomic force microscopy (AFM) studies confirmed that these polymers were highly extended at temperatures close to Tp in physiologically-relevant media. Importantly, NIH-3T3 cells were attached on the collapsed PNAGAm-PNPhAm brush surface at 30 C after 20 h incubation, while release of cells from the extended brushes was observed within 2 h after the culture temperature was switched to 37 C. Furthermore, the changes in cell attachment followed changes in the Lewis base component of surface energy. The results indicate that, in contrast to the established paradigm of enhanced cell attachment to surfaces where polymers are above a Lower Critical Solution Temperature (LCST), these novel substrates enable detachment of cells from surfaces at temperatures above a UCST. In turn these responsive materials open new avenues for the use of polymer-modified surfaces to control cell attachment for applications in cell manufacture and regenerative medicine.